Tracking vessel in tissue culture laboratory using RFID system and LDR sensor / Nurul Syahrini Mat Koris - Mat Koris, Nurul Syahrini (2011)
Tissue culture laboratory at Malaysian Palm Oil Board (MPOB) is one place that involved in producing superior planting material through tissues culture or cloning process. In the tissue culture laboratory, a lot of vessels for cloning process are located in several racks with different growth rooms. All the data specification of vessels such as date, the person who doing the cloning process, and number of racks are recorded manually on log book for the future references. Besides that, the data of tracking the vessel such as time and who take out the vessels also done manually. This thesis proposed a project consists of Radio Frequency Identification (RFID) system with LDR sensor to replace the current method of data tracking vessels. This project consists of two main parts which are hardware and software. In hardware part, the main component is RFID card, RFID reader, PIC 16F877A, and Light Dependent Resistors (LDR) sensor to detect the vessels. Meanwhile, for the software part, visual basic software is used to display the information or data. Tested has been performed and the result show the improvement of the tracking vessel system in the tissue culture laboratory.